I Dress Like Everyone, I Dress Like No Other - Volchenkov, D.; Banaszak, E.; Kocjan, K.; Kr, T (Discontinuity, Nonlinearity, and Complexity, 2026)
By a successive reduction of complexity in the appearance data collected in situ, we have shown that the way people maintain their appearance constitutes a multi-level dynamical process evolving in several incomparable time scales. The slowest component of this process represents a gradual diffusion of features (with a measurable pace of growing variance) from a proto-costume, which is likely has the 19th century military uniform as a prototype for men, and a robe de soirée - for women. The rapidly varying component of the process is statistically reminiscent of adiabatic processes in thermodynamics which evolve rapidly, without exchange of heat of a system with its environment. The appearance of other people can be considered as being in a state of "thermal equilibrium" between the almost imperceptible, subtle modifications of a traditional costume and the one day gusts of unpredictable fashion.